Aromatherapy with Isopropyl Alcohol versus Intravenous Ondansetron in Management of Mild Brain Trauma Nausea and Vomiting; a Randomized Clinical Trial - Rezvani Kakhki, Behrang; Ghasemi, Tahereh; Vafadar Moradi, Elnaz; Abbasi Shaye, Zahra; Mousavi, Seyed Mohammad (Archives of Academic Emergency Medicine, 2022)
Introduction: Nausea and vomiting are common complaints among patients who refer to the emergency department with head trauma. This study aimed to compare the effect of aromatherapy with isopropyl alcohol versus intravenous ondansetron in management of mild head trauma nausea and vomiting. Methods: This randomized clinical trial was conducted on patients with isolated mild head trauma complaining of nausea and vomiting who were referred to emergency department during a 6-month period. Patients were randomly divided into control (IV ondansetron + aromatherapy with saline) and intervention (IV saline + aromatherapy with isopropyl alcohol) groups. The frequency of vomiting and the severity of nausea (from 0 to 100 with the verbal scaling) were written before, and 10 and 30 minutes after intervention and compared between groups. Results: A total of 210 patients (105 patients in each group) with a median age of 38 years were included in the study, 112 (54.3%) of which were male. Ten minutes after aromatherapy, no significant difference was observed in nausea and vomiting between the two groups (p >0.05). Nausea score after 30 minutes (p = 0.015) was significantly lower in the intervention group compared to the control group, but vomiting after 30 minutes (p <0.001) was higher in the intervention group. Conclusion: Aromatherapy using isopropyl alcohol significantly reduced nausea of patients with mild isolate head trauma after 30 minutes. Regarding vomiting, no favorable result was observed in this study. However, the frequency of vomiting was reduced in both control and intervention groups.